Factors influencing success of artificial insemination of pigs using extended fresh semen in rural smallholder pig farms of Rwanda - Munyaneza Celestin1*, Nyiramuhire Valentine1 , Mubashankwaya Isaac1,2 , Munyandamutsa Fabrice , Ndisanze Oscar , Bagaragaza François, Mujyambere Jean Marie Vianey (African Journal of Pig Farming, 2020)
The present study was conducted to analyse the factors influencing the success of artificial insemination (AI) in pigs using extended fresh semen in rural smallholder pig farms. One hundred female pigs from Rulindo and Gicumbi districts in Northern Region of Rwanda were artificially inseminated using locally collected and extended fresh semen. The pregnancy was confirmed by using both no returns to estrus and abdomen palpation at 21 and two and half months post insemination, respectively. The factors influencing the success of AI were analysed using one way analysis of variance (ANOVA) test. The results showed that the number of inseminations per conception (IC) and litter size were 1.89 ± 0.83 and 7.94 ± 2.24, respectively. The number of AI per conception was significantly influenced (p < 0.05) by intrinsic factors (age and parity of the female pig) and extrinsic factors (sex, age and education of household head, time of AI and distance between the farm and semen collection center). The litter size was significantly influenced (p < 0.05) by parity. From the results, we recommend establishing more semen production centers and providing more training on pig management and AI.